Comparison of Ocular Ultrasonography and Magnetic Resonance Imaging for Detection of Increased Intracranial Pressure - Patterson, David F.; Ho, Mai-Lan; Leavitt, Jacqueline A.; Smischney, Nathan J.; Hocker, Sara E.; Wijdicks, Eelco F.; Hodge, David O.; Chen, John Jing-Wei (Frontiers in Neurology, 2018)
Background/Aims: To evaluate and compare the performance of ocular ultrasonography (US) and magnetic resonance imaging (MRI) for detecting increased intracranial pressure (ICP) in patients with idiopathic intracranial hypertension (IIH). Methods: Twenty-two patients with papilledema from IIH and 22 with pseudopapilledema were prospectively recruited based on funduscopic and clinical findings. Measurements of optic nerve sheath diameters (ONSD) 3 mm behind the inner sclera were performed on B-scan US and axial T2-weighted MRI examinations. Pituitary-to-sella height ratio (pit/sella) was also calculated from sagittal T1-weighted MRI images. Lumbar puncture was performed in all patients with IIH and in five patients with pseudopapilledema. Results: Average US and MRI ONSD were 4.4±0.7 and 5.2±1.4 mm for the pseudopapilledema group and 5.2±0.6 and 7.2±1.6 mm for the papilledema group (p<0.001). Average MRI pit/sella ratio was 0.7±0.3 for the pseudopapilledema group and 0.3±0.2 for the papilledema group (p<0.001). Based on receiver-operator curve analysis, the optimal thresholds for detecting papilledema are US ONSD >4.8 mm, MRI ONSD >6.0 mm, and MRI pit/sella <0.5. Combining a dilated US ONSD or MRI ONSD with a below-threshold MRI pit/sella ratio yielded a sensitivity of 73% and specificity of 96% for detecting IIH. Adding the US ONSD to the MRI ONSD and pit/sella ratio only increased the sensitivity by 5% and did not change specificity. Conclusions: US and MRI provide measurements of ONSD that are well-correlated and sensitive markers for increased ICP. The combination of the ONSD and the pit/sella ratio can increase specificity for the diagnosis of IIH.